A novel high‐throughput setup for in situ powder diffraction on coin cell batteries. (21st January 2016) - Herklotz, Markus; Weiß, Jonas; Ahrens, Eike; Yavuz, Murat; Mereacre, Liuda; Kiziltas-Yavuz, Nilüfer; Dräger, Christoph; Ehrenberg, Helmut; Eckert, Jürgen; Fauth, Francois; Giebeler, Lars; Knapp, Michael
Abstract : A novel integrated high‐throughput sample holder for in situ X‐ray powder diffraction of coin cell batteries was developed and successfully tested for precision and reliability with a silicon standard and spinel‐based positive electrode materials for Li‐ion batteries. Abstract : A new setup for in situ experiments with up to eight electrochemical cells, especially battery coin cells, and the corresponding custom‐made in situ cells are presented. The setup is primarily optimized for synchrotron powder diffraction measurements. As a newly constructed experimental setup, the in situ coin cell holder was tested for positional errors of the cells and the reliability of the diffraction as well as electrochemical measurements. The overall performance characteristics of the sample holder are illustrated by measurements on LiMn2 O4 and LiNi0.35 Fe0.3 Mn1.35 O4 spinel‐based positive electrode materials.